A new scramble for Africa? imperialism, investment and development - edited by Roger Southall (Scottsville University of KwaZulu-Natal Press, 2009)
Dramatically escalating prices of raw materials - driven by rapid industrialization in China and other countries of the global South, as well as by looming world shortages - had, for the few years preceding the financial meltdown and global recession of 2009, promoted a new scramble for Africa's natural resources. It signaled a brisk turnaround in prospects for what The Economist had dubbed the 'hopeless continent' as recently as 1999. However, while average growth rates across the continent have increased, the implications for Africa's development were, and remain at best, dubious. In this important book, the new scramble for Africa is placed in the historical context of imperialism, as the contributors show important continuities with the original 19th-century scramble. However, while the previous scramble was between major European powers, today the continent provides a battleground for competition between the US, the European Union, China, and other emerging players, such as India and South Africa. This book raises significant questions relating to: the nature of emerging global competition between the US and China; the centrality of the struggle for oil and minerals and resulting militarization; the international battle to capture Africa's markets; the marginalization of African capitalism; and the ambiguous benefits that investment and production by multinational companies bring to African communities. Arguing that exploitation of the continent by comprador African elites remains central, the book concludes by raising important questions about the prospects for development in Africa.
Collection subset: Management and Business Studies
Keywords: Investments, Foreign -- Africa; Economic development -- Africa; Africa -- Foreign economic relations; Africa -- Economic conditions -- 21st century